Educational Management of Pesantren in Digital Era 4.0 - Abidin, Zaenal (Jurnal Pendidikan Agama Islam, 2020)
In the digital era 4.0, the necessary e-learning skills of the santri at the Gontor 12 Tanjung Jabung Timur modern Islamic boarding school are fundamental to be included in the pesantren education management system. The goal is to improve the students' skills to be highly competitive with other public school graduates. This research examines the education management applied and the learning methods implemented to support the students' skills at the boarding school. The methodology used in this study is a qualitative descriptive approach with a type of case study. This approach can clearly explain the phenomena of the research phenomena and entirely from the new findings at the Pondok Pesantren Modern Darussalam Gontor 12 Tanjung Jabung Timur. This study indicates new effective methods to support e-learning-based santri skills through the learning process using the Yadan-Biyadin method. Yadan-biyadin is a method of conveying material from one hand to another or from one santri to another.